O ciclo intercultural de iniciação acadêmica para estudantes indígenas da Universidade Estadual de Londrina - Alves, Roseli (2016)
The implementation of the State LawN°. 13,134 / 2001, modified later by the Law N°. 14,995 / 2006, established the creation of additional places for the indigenous peo-ples in public universities in the state of Paraná. Since then several strategies were created by the University Commission for the Indians (CUIA) in order to strengthen the admission, continuity and graduation for indigenous university students from Paraná s Higher Education Institutions (HEIs) benefited by the law. Among those strategieslies the implementation experience of theLondrina State University (UEL)Intercultural Cycle for Academic Initiation which was created in 2013 and im-plemented early 2014. Upon successful admissionin the Indigenous Peoples Ad-mission Exam, it is mandatoryforenrolled students to attend the Cycle during a year and if approved they can be enrolled in an undergraduate course of their choice. TheCycle program aims to strengthen the permanence of these students at UEL, reducing college dropouts and consequently raising graduationrates. This research goes over, first, CUIA-State s contributions which figures as main guiding head for permanence policies within the HEI s then shows CUIA-UEL sdemands and sub-sequently describes the cycle as an indispensable action tool for the strengthening of affirmative action public policy in Paraná. The theoretical framework presents es-pecially the contributions of researchers from affirmative action and inclusion of in-digenous peoples in the State of Paraná universities, the understanding of Ethnic Boundariesby Fredrik Barth (1998), Bourdieu's Field Theory (1996), relations be-tween "colonizers" and "colonized" taught by Balandier (1969) in the field of political anthropology, following methodological guidelines for the case study addressed by Yin (2001) and the semi-structured interview was used recorder technique accord-ing to Queiroz (1991). The study's methodology is based on watching meetings and activities of the Intercultural Cycle and actions by the University Committee for the Indians (CUIA); interviewing (in a semi-structured way) members of the open CUIA, as well as Cycle sstudentsand educators; reviewingliterature about the subject; and analyzing normative acts among Cycle s creation and operation. It is expected from this work to reflect over the prospectsof increased coverage of the "Intercultural Cy-cle" in the public universitiesof Paraná.